Studi Empiris Penentu Kinerja Keuangan Perusahaan - Bimawan, Fitnantyo (Graha Akuntansi, 2022)
This study aimed to analyze the influence of variables Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Net interst Margin (NIM), and the Capital Adequacy Ratio (CAR) of the Return On Asset (ROA). Testing the hypothesis in this study using multiple regression analysis (Multiple Regression). The sample used in this study were 29 banking companies listed in the Indonesia Stock Exchange (IDX) with a purposive sampling techniques, namely engineering samples based on the determining criteria. Those criteria are banking companies listed on the Stock Exchange in 2012 - 2015 and submit annual financial statements and complete. The results of the study after partial hypothesis test showed that the CAR had no significant positive effect on ROA, LDR significant negative to ROA, significant negative NPL to ROA and NIM has a positive and significant impact on ROA.